2022
DOI: 10.3390/healthcare10020213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rehabilitation Models on Self-Stigma among Persons with Mental Illness

Abstract: Social stigma is inevitable for mentally ill patients, but how patients treat themselves is a priority for rehabilitation and an important buffer mechanism. This study thus aimed to measure the effectiveness of rehabilitation models for improving self-stigma. This quasi-experimental research design applied purposeful sampling. The participants (n = 250) were persons with mental illness who received rehabilitation treatment in central Taiwan. They were divided into community- (n = 170) and institution-based (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The sample size needed for serial mediation was calculated using the Monte Carlo Power Analysis webpage (Schoemann et al., 2017). Referencing the correlation coefficients reported in previous studies, the correlation coefficients between self‐stigma and social support, between self‐stigma and perceived hope, between self‐stigma and perceived recovery, between social support and perceived hope, between social support and perceived recovery, and between perceived hope and perceived recovery were set to −.353 (Li et al., 2021), −0.582 (Lim et al., 2020), 0.560 (Lim et al., 2020), 0.219 (Mutschler et al., 2022), and 0.641 (Sari et al., 2021), respectively; referencing previous relevant studies that used the tools expected to be employed in this study, the standard deviations for self‐stigma, social support, perceived hope and perceived recovery were set to 10.83 (Lin et al., 2022), 15.48 (Prabhakaran et al., 2021), 5.02 (Lim et al., 2020), and 9.04 (Yang & Lo, 2017), respectively. The calculation by the webpage indicated that when the sample size was 110, the power was 0.97.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size needed for serial mediation was calculated using the Monte Carlo Power Analysis webpage (Schoemann et al., 2017). Referencing the correlation coefficients reported in previous studies, the correlation coefficients between self‐stigma and social support, between self‐stigma and perceived hope, between self‐stigma and perceived recovery, between social support and perceived hope, between social support and perceived recovery, and between perceived hope and perceived recovery were set to −.353 (Li et al., 2021), −0.582 (Lim et al., 2020), 0.560 (Lim et al., 2020), 0.219 (Mutschler et al., 2022), and 0.641 (Sari et al., 2021), respectively; referencing previous relevant studies that used the tools expected to be employed in this study, the standard deviations for self‐stigma, social support, perceived hope and perceived recovery were set to 10.83 (Lin et al., 2022), 15.48 (Prabhakaran et al., 2021), 5.02 (Lim et al., 2020), and 9.04 (Yang & Lo, 2017), respectively. The calculation by the webpage indicated that when the sample size was 110, the power was 0.97.…”
Section: Methodsmentioning
confidence: 99%